Update on trends in varicella mortality during the varicella vaccine era-United States, 1990-2016 - Jessica Leung; Mona Marin (Taylor & Francis Group, 2018)
We reported previously that the annual average mortality rate in the United States in 2008-2011 for varicella listed as the underlying cause declined 87% compared with the prevaccine period (1990-1994). Here, we update the analysis with five additional years of data. We used varicella death data from the 2012-2016 Mortality Multiple Cause-of Death records to calculate mortality rates during 2012-2016 and trends since the prevaccine period and end of 1-dose vaccination program (2005-2007). The annual average age-adjusted mortality rate for varicella as the underlying cause was 0.03 per million population during 2012-2016, a 94% reduction from prevaccine years and a 47% reduction from 2005-2007. Varicella deaths continue to decline due to the varicella vaccination program in the United States.